The Peace of St. Cuthbert - Craster, Edmund (The journal of ecclesiastical history, 1957)
The elder James Raine published in 1839 as appendix no. CCCXXXII to his edition of Historiae Dunelmensis Scriptores Tres a document entitled ‘Consuetudo et lex sancti patris Cuthberti’. Attention was subsequently drawn to it, in 1905, by Professor Lapsley. As Lapsley was only concerned in his article with the status of drengs, he forbore to enter into what he called ‘the quellenkritik of this curious document’, and, as we shall see, he mistook its date. It is therefore worth while carrying investigation further.